Antenatal and postnatal maternal depressive symptoms and trajectories and child hospitalization up to 24 months of life: findings from the 2015 Pelotas (Brazil) birth cohort study - Jacques, N; Mesenburg, MA; Murray, J; Bertoldi, AD; Domingues, MR; Stein, A; Silveira, MF (Elsevier, 2021)
Objective To examine the association between antenatal and postnatal maternal depression symptoms, and child hospitalization during the first 2 years of life in the 2015 Pelotas Birth Cohort Study. Study design This is an observational study. Maternal depressive symptoms of 4275 mothers were measured using the Edinburgh Postnatal Depression Scale. Hospitalization of the child for any reason was assessed using maternal report. Bivariate analysis and multivariate Poisson regressions were used to assess the association between maternal depressive symptoms and child hospitalization. Results Compared with children of mothers with low depressive symptoms, children whose mothers experienced significant antenatal depressive symptoms were 1.74 (95% CI, 1.16-2.60) times more likely to be hospitalized by 3 months of age, and 2.14 (95% CI, 1.46-3.14) times more likely up to 24 months. For children whose mothers experienced severe postnatal depressive symptoms at 3 months, the risks for hospitalization by age 12 months were 1.84 (95% CI, 1.39-2.45) higher than children whose mothers had low depressive symptoms. There was an increased risk of hospitalization for children according to the severity of depressive trajectories across time. Conclusions Maternal depressive symptoms are a risk factor for hospitalization in children up to 2 years of age, and this risk increases with increased severity of depression. These results have public health relevance for decreasing the risk factors in mothers that can lead to hospitalization in children.